Case Report: Molecular Diagnosis Revealing an Intestinal Infection of a Hybridized Tapeworm (Taenia saginata and Taenia asiatica) to Human in Yunnan, China - Chu, Kan-Kan; Qiu, Ye; Liao, Ce-Heng; You, Zhi; He, Zuo-Shun; Fang, Wen; Li, Hong-Ying; Daszak, Peter; Hu, Jun-Jie; Zhang, Yun-Zhi; Ge, Xing-Yi (Frontiers in Gastroenterology, 2022)
Human taeniasis caused by tapeworms is an intestinal disease prevalent in many countries around the world. Taenia asiatica, Taenia saginata, and Taenia solium are the most common pathogens causing human taeniasis. Among the three species of tapeworms, T. saginata and T. asiatica share high similarity in their genomes and have been reported to be capable of hybridization with each other. Here, we reported a case of an 18-year-old male patient hospitalized in Yunnan Province, China, in 2019. Due to long-lasting abdominal distension and white tapeworm segments in the feces, the patient was diagnosed with taeniasis. He was treated with traditional Chinese medicine, and a tapeworm approximately 2.7 m long was expelled. The morphology of the eggs and gravid proglottids of the tapeworm was observed. Interestingly, the tapeworm was identified as a hybrid between T. saginata and T. asiatica according to molecular and phylogenetic analyses. This case is the first documented case of human taeniasis caused by a T. saginata and T. asiatica hybrid in Yunnan Province. Molecular evidence suggests that the hybrid of T. saginata and T. asiatica may have caused widespread infection in rural areas of Western China, and further investigation and research on these parasites in Western China are needed. The method described in this case may be helpful for future research.